Bioleaching of iron from laterite soil using an isolated Acidithiobacillus ferrooxidans strain and application of leached laterite iron as Fenton's catalyst in selective herbicide degradation. - Bhaskar S; Basavaraju Manu; Sreenivasa M Y (PLoS ONE)
A novel isolated strain Acidithiobacillus ferrooxidans BMSNITK17 has been investigated for its bioleaching potential from lateritic soil and the results are presented. System conditions like pH, feed mineral particle size, pulp density, temperature, rotor speed influences bioleaching potential of Acidithiobcillus ferrooxidans BMSNITK17 in leaching out iron from laterite soil. Effect of sulfate addition on bioleaching efficiency is studied. The bioleached laterite iron (BLFe's) on evaluation for its catalytic role in Fenton's oxidation for the degradation of ametryn and dicamba exhibits 94.24% of ametryn degradation and 92.45% of dicamba degradation efficiency. Fenton's oxidation performed well with the acidic pH 3. The study confirms the role of Acidithiobacillus ferrooxidans in leaching iron from lateritic ore and the usage of bioleached lateritic iron as catalyst in the Fenton's Oxidation.